CONTRIBUȚII CU PRIVIRE LA PORTRETUL LUI SIGISMUND DE LUXEMBURG DE PE POARTA MĂNĂSTIRII DIN BRAȘOV - POPICA, Radu (Studia Universitatis Babeș-Bolyai Historia Artium, 2017)
Contributions Regarding the Portrait of Sigismund of Luxembourg from the Gate of the Monastery in Brașov. The study provides data on the portrait of Sigismund of Luxembourg, located on the Monastery Gate in Brașov between the 16th and 19th centuries. A large wall painting, the portrait disappeared after the demolition of the gate in the years 1835-1836. The details of the mural painting depicting Sigismund of Luxembourg have so far remained largely unknown. Starting from a photograph, preserved at the Brașov County Administration of the National Archives, a reproduction of an easel painting, a true copy of the murals, the study reconstructs the aspect of the mural painting. The portrait of Sigismund of Luxembourg is one of the most important works of secular mural painting from 16th century Transylvania and remains so far unpublished in the speciality literature dedicated to the iconography of Sigismund of Luxembourg.